BASIC PRINCIPLES OF PRIMARY SURGICAL TREATMENT OF HEAD INJURIES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores the fundamental principles governing the primary surgical treatment of head injuries. It delves into the significance of understanding these principles, analyzes relevant literature to establish a comprehensive foundation, and outlines methods, results, and discussions to contribute to the ongoing improvement of surgical approaches. The conclusions drawn emphasize the critical nature of adhering to these principles for optimal patient outcomes, while suggesting avenues for further research and advancements in the field.